Health beliefs of women attending mammography unit and related factors - Kamile Altuntuğ; Emel Ege; Ganime Dilek Demlik; Hüseyin Özbiner; Şerife Kurşun (Journal of Contemporary Medicine, 2021)
Aim: This descriptive study was done to evaluate the perceptions of health beliefs and related factors of women attending a mammography unit for mammograms. Materials and Methods: It was carried out with 181 women admitted to a mammography unit of a university hospital. Data were measured using a questionnaire form. Results: Statistically significant differences were found between women's education (health motivation, Breast Self-Examination (BSE) benefits and barriers), BSE performance status (health motivation, BSE barriers and self-efficacy, mammography benefits and barriers) and family history of breast cancer (sensitivity, health motivation, BSE benefits) (p lt;0.05). As a result of the research findings, it was determined that 64.6% of women performed BSE. Conclusion: In accordance with these results, increasing the awareness training for breast cancer and the dissemination of screening may be suggested by taking into account the individual characteristics of women.